PELAKSANAAN PERJANJIAN JUAL BELI IKAN AROWANA SUPER RED (Scleropages Formosus) ANTARA PEMBELI DENGAN PENGUSAHA CV. MINDA DI PONTIANAK - NIM. A1012141236, ERI HIKMATUL BASYIR (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac CV. Minda is a company that provides pets, especially Super Red Arowana Fish (Scleropages Formosus). CV. Minda, whose address is Jalan Surva Gang Surya Nilai No 11 Pontianak, was founded in 1996 by a man by the name of H. Nofrizal. This company provides Super Red Arowana Fish (Scleropages Formosus) of various sizes from 10 cm super red Arowana Fish (Scleropages formosus) for Rp. 2,750,000, - to super red Arowana fish (Scleropages formosus) measuring 20 cm for Rp. 3,800,000. . Parties who do not have good faith generally must be responsible for their actions and must bear the risk. In the Civil Code, the provisions regarding good faith, especially those relating to the implementation of agreements stipulate that all agreements must be carried out in good faith. This means,